Development of Differentiated English Language Learning Multimedia - Monika Meriana Simamora; Sahat Siagian; Naeklan Simbolon (Randwick International of Education and Linguistics Science Journal, 2024)
This research and development aims to determine the feasibility and effectiveness of differentiated learning multimedia using Smart Apps Creator (SAC) in improving English learning outcomes for class VIII students at UTP SPF SMP Negeri 2 Sunggal. The type of research is research and development (R&D) using the ADDIE model, with stages: analysis, design, development, implementation, and evaluation. The research was conducted at UPT SPF SMP Negeri 2 Sunggal, class VIII students, consisting of 64 students, with 32 students in the experimental class taught using SAC multimedia and 32 students in the control class not using SAC multimedia. The research results show: (1) validation by material experts (94.44% of very feasible criteria), by media experts (94.17% of very feasible criteria), and by learning design experts (93.61% of very feasible criteria). The results of individual trials were 76.67% feasible criteria, small group trials were 88.33% very feasible criteria, and field trial results were 91.04% very feasible criteria. (2) There are differences in student learning outcomes between the experimental and control classes. The experimental class had an average learning outcome of 82.75; the control class had an average learning outcome of 61.63. Hypothesis testing using an independent t-test on the post-test scores of the experimental class and control class obtained a significance result (2-tailed) of 0.000, which means <0.05. It can be concluded that there are significant differences between classes that are taught using differentiated learning multimedia and classes that are not taught using multimedia. The development of differentiated learning multimedia using SAC for class VIII SMP students is effective in improving English learning outcomes.